2019
DOI: 10.1371/journal.pone.0210270
|View full text |Cite
|
Sign up to set email alerts
|

Environmental complexity: A buffer against stress in the domestic chick

Abstract: Birds kept in commercial production systems can be exposed to multiple stressors from early life and this alters the development of different morphological, immunological and behavioural indicators. We explore the hypothesis that provision of a complex environment during early life, better prepares birds to cope with stressful events as well as buffers them against future unpredictable stressful episodes. In this study, 96 one day old pullets were randomly distributed in eight pens (12 birds/pen). Half of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 76 publications
2
41
0
1
Order By: Relevance
“…Several studies have demonstrated reduced fearfulness in hens exposed to increased environmental complexity during rearing [ 25 , 26 , 27 , 28 ], including reduced fear when reared with perches in broiler breeders [ 29 ]. These early life experiences may act via desensitising the pullets to variable stimuli, increasing the exploration of their environments or improving their capacity to adapt and respond appropriately to stress-inducing environmental changes [ 30 , 31 ]. Free-range hens may particularly benefit from modifications of their rearing environments, as pullets are reared indoors but adult hens have outdoor access.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated reduced fearfulness in hens exposed to increased environmental complexity during rearing [ 25 , 26 , 27 , 28 ], including reduced fear when reared with perches in broiler breeders [ 29 ]. These early life experiences may act via desensitising the pullets to variable stimuli, increasing the exploration of their environments or improving their capacity to adapt and respond appropriately to stress-inducing environmental changes [ 30 , 31 ]. Free-range hens may particularly benefit from modifications of their rearing environments, as pullets are reared indoors but adult hens have outdoor access.…”
Section: Introductionmentioning
confidence: 99%
“…One major difference between CC and other housing scenarios is a reduced environmental complexity; CC hens in particular show behavioral, endocrine and immunological signs of stress. In general, environmental enrichment is known to reduce housing stress in birds [26,88,89], and the observation of higher H/L ratios in hens in CC supports this view. Moreover, Campderrich et al [26] demonstrated that laying hens in a complex environment have a better inflammatory response and higher lymphocyte proliferation when exposed to cold stress.…”
Section: Effect Of Housing Systems On the Immune System-possible Mechmentioning
confidence: 79%
“…In general, environmental enrichment is known to reduce housing stress in birds [26,88,89], and the observation of higher H/L ratios in hens in CC supports this view. Moreover, Campderrich et al [26] demonstrated that laying hens in a complex environment have a better inflammatory response and higher lymphocyte proliferation when exposed to cold stress. A recent review by Campbell et al [90], with focus on environmental enrichment during rearing on the behavioral and physiological development of laying hens, also concluded that stress-reducing effects of enrichment are associated with a positive effect on immune competence.…”
Section: Effect Of Housing Systems On the Immune System-possible Mechmentioning
confidence: 79%
See 1 more Smart Citation
“…For mammals, environmental heterogeneity has been found to play a significant role in foraging activities of caged coyotes compared to free range animals [ 10 ]. Chickens placed in more heterogeneous environments with a feeder, wood shavings, and wooden block perches presented a more refined repertoire of behaviours than chickens placed in an area with a feeder and wood shavings only [ 11 ]. Zebra fishes needed additional time to perform activities and were more stressed in simple environments compared to individuals placed in enriched water tanks with the presence of plastic plants, plastic shelter, gravel substrate and a novel object rotated every week [ 12 ].…”
Section: Introductionmentioning
confidence: 99%